Venezuela: Autocratic consolidation and splintered economic liberalization - Rosales, A; Jiménez, M (SciELO Agencia Nacional de Investigacion y Desarrollo, 2021)
In 2020, Venezuela has gone through a process of autocratic consolidation. This consolidation has taken place amid substantial economic reforms that have allowed the government of Nicolás Maduro survive sustained international and domestic pressure. In this article, we analyze this process of autocratic consolidation. We explain how, by focusing on the establishment of an “interim-government” in 2019, the Venezuelan opposition has been unable to coordinate an inclusive strategy to successfully bring about a democratic breakthrough and instead became further divided. We address the economic transformations witnessed in the country as policies of fragmented liberalization through opaque privatizations and an uneven multi-currency system, which have resulted from a deep recession, the collapse of the oil economy and sanctions. Finally, we discuss the implications of these political and economic processes for the social fabric of the country. We highlight that despite the government's attempts at criminalizing autonomous activism, the relative strengths of civil society allowed the survival of minimal democratic spaces that have spurred dialogue and resistance.